Exacerbation of Mania due to Metronidazole in a Bipolar Disorder Patient - Majed AlShakori; Savera I. Arain; Shabeer A. Thorakkattil; Syed Abdulkader (Case Reports in Psychiatry)
Bipolar disorder is a mental health disorder where the patient experiences extreme shifts in mood marked by depression, mania, or hypomania. It affects their overall daily life activities and sleep patterns. This case report is of a 74-year-old female patient with bipolar disorder who experienced a manic episode after initiation of antibiotics to treat gallbladder perforation with abscess formation. The patient’s past medical history included Parkinson’s disease, diabetes mellitus, bipolar disorder, and acalculous cholecystitis. The patient required hospitalization for a cholecystostomy tube insertion for drainage. During hospitalization, the patient was started on empiric treatment with broad-spectrum antibiotics, including piperacillin/tazobactam and metronidazole. The patient remained stable during the inpatient stay and was discharged home one week later. She was prescribed cefuroxime and metronidazole to complete a 2-week duration of antibiotics. However, upon discharge, she developed manic symptoms, including lack of need to sleep, excessive talking, and severe agitation. Upon assessment, the psychiatric team decided to hold metronidazole as it has an adverse effect of mania as evidenced in drug information resources. The patient started to show immediate recovery from the symptoms with complete resolution of manic symptoms on the 3rd day following the discontinuation of metronidazole. This case emphasizes the increased need for vigilance in bipolar patients upon prescribing metronidazole. Also, further research is needed to predict the time to onset of manic symptoms and improvement in patient symptoms upon drug discontinuation.